Highlighting the goals for Parkinson's care: commentary on NICE Guidelines for Parkinson's in Adults (NG71). (27th September 2018) - Brock, Peter; Fisher, James M; Hand, Annette; Walker, Richard W
Abstract: Parkinson's disease is a chronic multi-system disease that can cause motor and non-motor symptoms, cognitive changes and variably effective medications. Optimal management of the condition requires a multi-disciplinary team of healthcare professionals to work closely with the patient and their carers. The National Institute for Health and Care Excellence published updated guidelines on managing Parkinson's disease in adults in 2017. Here we discuss the implications of this guidance to current healthcare professionals involved in the care of people with Parkinson's disease. The guidance highlights the importance of clear communication with people with Parkinson's disease. We discuss examples of this, including providing a point of contact with specialist services for people with Parkinson's disease and ensuring information about the risks of impulse control disorders are given to people on dopaminergic therapy. The breadth of services required by people with Parkinson's disease is also described, including the need for access to physiotherapy, occupational therapy and speech and language therapy as well as treatment monitoring services for Clozapine. In addition, we emphasise the continued importance of ensuring people with Parkinson's disease receive their medications on time when in hospital or a care home.